2022
DOI: 10.3390/ijerph19063299
|View full text |Cite
|
Sign up to set email alerts
|

A New Combined Air Quality and Heat Index in Relation to Mortality in Monterrey, Mexico

Abstract: The negative synergistic effects of air pollution and sensible heat on public health have been noted in numerous studies. While separate, simplified, and public-facing indices have been developed to communicate the risks of unhealthful levels of air pollution and extreme heat, a combined index containing elements of both has rarely been investigated. Utilizing air quality, meteorology, and mortality data in Monterrey, Mexico, we investigated whether the association between the air quality index (AQI) and morta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 40 publications
(45 reference statements)
0
1
0
Order By: Relevance
“…Yet, there is no consistent method to communicate the combined risk. Fever et al [30] unified the HI and AQI for PM 2.5 and ozone in a combined index using several different models. They found that improved mortality predictions were possible with their combined indices in Monterrey, Mexico, but cautioned that their results might not be generalizable to regions with different air pollutant and weather patterns.…”
Section: Introductionmentioning
confidence: 99%
“…Yet, there is no consistent method to communicate the combined risk. Fever et al [30] unified the HI and AQI for PM 2.5 and ozone in a combined index using several different models. They found that improved mortality predictions were possible with their combined indices in Monterrey, Mexico, but cautioned that their results might not be generalizable to regions with different air pollutant and weather patterns.…”
Section: Introductionmentioning
confidence: 99%